A Study on Tourist Motivation for Doing Plastic Surgery in South Korea - Ayu Diah Lestari (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study examines the motivations of international tourists to undergo plastic surgery in South Korea, known for its advanced medical services and strong reputation in cosmetic surgery. Using a quantitative approach through an on-site survey conducted in the Gangnam area on May 2–3, 2024, data were collected from 40 respondents. Most participants were female tourists aged 21–30, mainly from China. Findings show that service quality is the primary factor influencing destination choice, followed by accessibility, and 82% underwent surgery to improve appearance rather than for medical reasons. Despite awareness of potential side effects, 90% remained willing to proceed. Overall satisfaction was high, indicating that Korea’s medical excellence and destination appeal strengthen its position in global medical tourism.